2020
DOI: 10.2214/ajr.19.22571
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dual-Phase FDG PET/CT in the Diagnosis and Follow-Up of Brain Tumors

Abstract: OBJECTIVE.-FDG PET/CT of brain tumors is limited by background activity. Dual-phase FDG PET/CT can eliminate this limitation and allow discernment of viable tumors. Our aim was to assess the diagnostic capability of dual-phase FDG PET/CT qualitatively and quantitatively and to determine cutoff values for dual-phase FDG PET/CT in brain tumor imaging. MATERIALS AND METHODS.-Retrospectively, 51 malignant brain tumors were evaluated with dual-phase FDG PET/CT in 32 patients. Acquisitions were performed 30 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…32 Several previous studies reported controversial and conflicting results of DTP 18 F-FDG PET/CT in various cancer type for differentiation of malignant from benign lesions. [8][9][10][33][34][35][36][37][38] In HCC patients, Oksuzoglu et al 33 showed that a significant increase in tumor SUV in delayed images in contrast to a significant decrease in background SUVs suggests that delayed images in HCC may contribute to diagnostic performance through a potential increase in the contrast between the tumor and background. According to studies performed in breast cancer patients, Yamagishi et al 34 showed that DTP 18 F-FDG PET/CT can be a useful method for predicting relapse in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…32 Several previous studies reported controversial and conflicting results of DTP 18 F-FDG PET/CT in various cancer type for differentiation of malignant from benign lesions. [8][9][10][33][34][35][36][37][38] In HCC patients, Oksuzoglu et al 33 showed that a significant increase in tumor SUV in delayed images in contrast to a significant decrease in background SUVs suggests that delayed images in HCC may contribute to diagnostic performance through a potential increase in the contrast between the tumor and background. According to studies performed in breast cancer patients, Yamagishi et al 34 showed that DTP 18 F-FDG PET/CT can be a useful method for predicting relapse in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a mass adjacent to the tracheal wall is likely to be regarded as the base of the tumor from cross-sectional observation, which reduces the accuracy of observation. It has been demonstrated that 3D images of the central trachea are useful complements to crosssectional images, and that multi-slice spiral CT provides a clearer view of tracheal tumors, reduces the possibility of false positives, and effectively screens recurrence after treatment [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…This hampers its sensitivity and diagnostic accuracy in detecting glial lesions. Few studies in the literature have shown improved lesion detection and diagnostic accuracy in the assessment of brain lesions by using dual time point imaging at 30 min (time point 1) and 3 h (time point 2) [19]. Glucose loading prior to FDG injection has been demonstrated to be a valuable adjunct to improve the diagnostic accuracy of FDG PET/ CT in brain tumors [20].…”
Section: Discussionmentioning
confidence: 99%